VARSHAM NIKITOVICh ERMYАN - Adilov Farkhod Abduvalievich (Modern American Journals, 2025)
In the 20th century, Uzbekistan also experienced positive changes and developments in the field of fine arts, including a number of artists who dedicated their lives to the development of this field. Varsham Nikitovich Ermyan's toothe place is incomparable. In this articlePeople's artist of Uzbekistan Varsham Nikitovich ErmyanThe creative work of the author is discussed and hisabout his work and creativity in the field of fine artsinformation is provided.
Keywords: Art, artist, international, film studio, visual arts, producer, portrait, caricature, color image, graphic, book, poster, photograph.